THE DYNAMICS OF MUHAMMADIYAH'S PRESERVATION AND ITS CHARACTERISTICS IN EDUCATION IN SIKKA DISTRICT, FLORES, NTT. - Ibnu Mas’ud (Universitas Islam Negeri Alauddin Makassar, 2019)
This paper discusses the Muhammadiyah Association in Sikka Flores Regency, East Nusa Tenggara. Because this study is a qualitative study, the authors use an educational approach, a sociological approach and a religious approach as an analysis tool to approach the study in question. The source of scientific data obtained from the management, leaders and cadres Persyarikatan Muhammadiyah in Sikka Regency; school principals, teachers and students at Muhammadiyah schools in Sikka Regency; document; and observations. The instruments used were observation guidelines, interview guidelines, and documentation. Data analysis techniques are data reduction, data display, and data verification. Triangulation is used to test the validity of the data. The researcher came to the conclusion that Muhammadiyah thought had been in contact with Muslim Sikka Regency since 1937, brought by Mr. Husaini Daeng Maramba who came from Selayar, South Sulawesi. Many obstacles faced by Persyarikatan Muhammadiyah Sikka Regency, including: multiple positions, lack of human resources, lack of funds and land, lack of maximum cadre enthusiasm and Muslim awareness of the importance of education are still lacking. Various efforts have been made including: regeneration, withdrawal of contributions, submission of proposals for aid, establishing cooperation, finding land outside Muslim villages, undertaking religious and familial approaches, exemplary, earnest sacrifice, earnest determination and earnest effort, ta'awun between business charity and sincerity are the basis in every movement.